Preface: 4th International Symposium on Education and Social Sciences (ESS 2023) - Chen, Yuanyuan; Sarah, Dieter (Transactions on Social Science, Education and Humanities Research, 2024)
4th International Symposium on Education and Social Sciences (ESS 2023) was held during December 30-31, 2023. This 4th ESS was successfully held offline - Xi’an City and online - Tencent Meeting platform.The aim of the conference is to provide an interactive platform for the academicians, R & D organizations, industries, innovators, entrepreneurs, government agencies and policy-makers etc., from both China and abroad to exchange ideas on recent researches and advances in the domain of education and social sciences with its prospective application in the various interdisciplinary domains of engineering. This two-day conference was being organized in technical association with Research Center of Engineering and Science and included invited keynote talks and oral paper presentations from both academia and industry to ignite our young minds, to initiate them in the field of meaningful research and thereby enrich their existing knowledge.ESS 2023 had gained respect in the scientific community with consistent hard work of its organizers. The objective of publishing this proceedings is to record, acknowledge, and share the cherished contribution made by the symposium participants. This collection contains over 20 peer-reviewed papers selected from over 50 submissions.With our warmest regards,Yuanyuan ChenDieter SarahConference Committees